Novel application of high‐dose rate brachytherapy for severe, recalcitrant palmoplantar pustulosis. (5th February 2016) - Timerman, D.; Devlin, P. M.; Nambudiri, V. E.; Wright, N. A.; Vleugels, R. A.; Clark, R. A.; Kupper, T. S.; Merola, J. F.; Patel, M.
Summary: Palmoplantar pustulosis (PPP) is a chronic pustular dermatitis of the palms and soles, which is frequently associated with significant pruritus and pain, often limiting daily activities. We present the case of a 36‐year‐old man with severe PPP who had treatment failure with multiple medical therapies but showed marked improvement with high‐dose rate brachytherapy. Brachytherapy has the advantage of providing a conformal dose distribution over complex curved surfaces, such as the foot and ankle. Our observations suggest that brachytherapy may be a well‐tolerated treatment option for patients with severe, refractory PPP.